Scaling up anodic TiO2 nanotube layers - Influence of the nanotube layer thickness on the photocatalytic degradation of hexane and benzene - Sopha, Hanna Ingrid; Baudys, Michal; Hromádko, Luděk; Lhotka, Miloslav; Pavlinak, David; Krysa, Josef; Macák, Jan (Elsevier Science BV, 2022)
In this work, the preparation of homogenous TiO2 nanotube (TNT) layers with different thicknesses via anodization on Ti substrates with a large geometrical area of two times 5 cm x 10 cm (i.e. both sides of the Ti substrate) is shown for the first time. TNT layers with four different thicknesses of similar to 0.65 µm, similar to 1 µm, similar to 7 µm, and similar to 14 µm were prepared with excellent conformality and homogeneity over the anodized area. These TNT layers were successfully employed as photocatalysts for the degradation of hexane and benzene as model compounds in the gas phase under ISO standards, showing an increase of the conversion for both model compounds with the TNT layer thickness. While a stable hexane conversion was observed for all TNT layers during the measuring time of three hours, in case of benzene degradation an initial conversion decrease was monitored before the conversion stabilized. Despite this trend, SEM and XPS analyses did not reveal any significant amount of reaction products on the TNT layer surface.
Zvětšování ploch vrstev anodických nanotrubiček TiO2 - Vliv tloušťky vrstvy nanotrubiček na fotokatalytickou degradaci hexanu a benzenu
Keywords: TiO2 nanotube layers; anodization; large areas; upscaling; gasphase photocatalysis; vrstvy nanotrubiček; TiO2,anodizace; velké plochy; upscaling; plynovéfáze fotokatalýza